2019
DOI: 10.34133/2019/6956937
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Color Lasing Lines from EMPs in Diluted Magnetic Semiconductor CdS:NiI Structure

Abstract: Have one ever seen a semiconductor that can issue two-color lasing lines? The diluted magnetic semiconductor (DMS) can do this. Here, we have observed dual lasing lines of 530 nm and 789 nm from a DMS structure of CdS:NiI, in which the excitonic magnetic polaron (EMP) and localized excitonic magnetic polaron (LEMP) are excitations out of ferromagnetic (NiS)x Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…19,20 Also, there are many studies on the near-infrared laser emission of CdS nanowires/ nanobelts by doping Mn(II) or Ni ions. 21,22 What is more, surface-plasmon-enhanced lasing at room temperature is also studied before. 23,24 However, it is rare to achieve lasing at continuous wave (CW) laser excitation just in doped nanowires by one-step growth because the much lower This article is made available for a limited time sponsored by ACS under the ACS Free to Read License, which permits copying and redistribution of the article for non-commercial scholarly purposes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Also, there are many studies on the near-infrared laser emission of CdS nanowires/ nanobelts by doping Mn(II) or Ni ions. 21,22 What is more, surface-plasmon-enhanced lasing at room temperature is also studied before. 23,24 However, it is rare to achieve lasing at continuous wave (CW) laser excitation just in doped nanowires by one-step growth because the much lower This article is made available for a limited time sponsored by ACS under the ACS Free to Read License, which permits copying and redistribution of the article for non-commercial scholarly purposes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Liu et al reported the trap-state whispering-gallery mode lasing from high-quality tin-doped CdS whiskers at an ultralow threshold power under the excitation of femtosecond laser pulses, which indicated potential applications like low-threshold tunable micro/nanoscale lasers by these surface-doped semiconductor structures . In ZnO nanostructures, there are also cavity modes lasing at relatively low threshold because of the microcavity enhancement effect. , Also, there are many studies on the near-infrared laser emission of CdS nanowires/nanobelts by doping Mn­(II) or Ni ions. , What is more, surface-plasmon-enhanced lasing at room temperature is also studied before. , However, it is rare to achieve lasing at continuous wave (CW) laser excitation just in doped nanowires by one-step growth because the much lower power of a CW laser than that of a pulsed laser cannot produce population inversion, and a non-negligible thermal effect from the continuous interaction of the light and nanostructures largely hinders the generation of lasing. Here, we realized both band-edge and in-gap WGMs lasing in single Sn-doped nanowire excited by a CW 405 nm laser at 80 K, and such significant enhancement of the luminescence is attributed to local plasma forming by different valence Sn ions and enhanced cavity effect at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…People would ask if it is possible to use DMS to get the efficient spin-polarized luminescence or lasing in DMS, the answer is yes. We have found EMP formation in bulk DMS with ferromagnetic coupling pairs, ,, by which the collective EMPs could be excited to produce single-mode bosonic lasing. The single-mode lasing phenomenon represented the optical spin polarization in DMS.…”
Section: Resultsmentioning
confidence: 92%
“…Clearly, it is proved that EMP has strong relations with the optical spin polarizations. , The optical spin polarization would bind more excitons for the condensate to coherently emit light. In early reports, the ZnO:Mn film or powders show a bad optical spin polarization effect because it is found that the spin polarization effect in ZnO needs the A1 LO phonon coherent coupling assistance besides the unidirectional crystal orientation, ,, while there is no long-range LO phonon coupling with the exciton in their film and powders. Hence, spin coupling in a definite spatial range also plays a role in the photoinduced spin polarization; the random local crystal orientation in a sample is not good for spin polarization if no extrinsic field is added.…”
Section: Resultsmentioning
confidence: 99%
“…Specially, 1D single-crystalline wide-bandgap II-VI semiconductors, such as CdS with a direct band gap of 2.6 eV at room temperature, were studied widely due to their excellent photonics, electronics and optoelectronics properties. There are lots of reports on the CdS nanowire/nanobelt lasers, optical waveguides, photodetectors, field effect transistors and logic devices [5][6][7][8]. Many intrinsic carrier interactions, such as: electron-hole plasma, electronphonon coupling, exciton-phonon scattering, excitonexciton interaction and excitonic polariton, take effect in a new way in the nanometer-scale [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%